2018
DOI: 10.1038/s41591-018-0012-z
|View full text |Cite
|
Sign up to set email alerts
|

ARID1A deficiency promotes mutability and potentiates therapeutic antitumor immunity unleashed by immune checkpoint blockade

Abstract: ARID1A (the AT-rich interaction domain 1A, also known as BAF250a) is one of the most commonly mutated genes in cancer1,2. The majority of ARID1A mutations are inactivating mutations and lead to loss of ARID1A expression3, which makes ARID1A a poor therapeutic target. Therefore, it is of clinical importance to identify molecular consequences of ARID1A deficiency that create therapeutic vulnerabilities in ARIDIA-mutant tumors. In a proteomic screen, we found that ARID1A interacts with mismatch repair (MMR) prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

33
394
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 428 publications
(433 citation statements)
references
References 34 publications
33
394
4
2
Order By: Relevance
“…Conversely, ARID1A inactivation (mostly from inactivating mutations) compromised MMR and increased mutagenesis. In line with our results, the recent study found that tumors formed by an ARID1A‐deficient ovarian cancer cell line in syngeneic mice displayed increased mutational load and PD‐L1 expression . Notably, treatment with anti‐PD‐L1 antibody reduced tumor burden and prolonged the survival of mice bearing ARID1A‐deficient, but not ARID1A‐wild‐type, ovarian tumors .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Conversely, ARID1A inactivation (mostly from inactivating mutations) compromised MMR and increased mutagenesis. In line with our results, the recent study found that tumors formed by an ARID1A‐deficient ovarian cancer cell line in syngeneic mice displayed increased mutational load and PD‐L1 expression . Notably, treatment with anti‐PD‐L1 antibody reduced tumor burden and prolonged the survival of mice bearing ARID1A‐deficient, but not ARID1A‐wild‐type, ovarian tumors .…”
Section: Discussionsupporting
confidence: 91%
“…One recent study has found that ARID1A can interact with mismatch repair (MMR) protein MSH2 and recruit MSH2 to chromatin during DNA replication and promoting MMR . Conversely, ARID1A inactivation (mostly from inactivating mutations) compromised MMR and increased mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…ARID1A may play a role in response to therapy and further investigation is required to establish the impact of ARID1A status for treatment. Recently, a study suggested that ARID1A deficiency contributes to impaired mismatch repair and mutator phenotype in cancer, and may cooperate with immune checkpoint blockade therapy [30].…”
Section: Discussionmentioning
confidence: 99%
“…The SWI/SNF complexes can be further classified into sub complexes. In most of these cancers, loss of functions due to inactivating mutations in BAF250a is observed [8,9]. BAF250a (ARID1a) gene is evolutionarily conserved and shows sequence similarities with yeast SWI1 and Drosophila protein Osa, which are components of SWI/SNF complexes in these organisms.…”
mentioning
confidence: 99%
“…Association of ARID-containing proteins BAF250a (also known as ARID1a) and BAF250b (also known as ARID1b) with the SWI/SNF complex results in BAF-A and BAF-B complexes respectively, whereas the association of ARID-containing BAF200 (also known as ARID2) results in PBAF complex [1][2][3][4]. Of the three ARID-containing proteins in the mammalian SWI/SNF complexes, only BAF250a has been classified as an essential and a tumor suppressor protein [8][9][10]. BAF250a has been shown to have a role in transcriptional co-activation induced by steroid hormones [1].…”
mentioning
confidence: 99%